2016
DOI: 10.1111/ane.12690
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral hemiparesis in ischemic stroke patients

Abstract: Most patients with ipsilateral hemiparesis had a past history of stroke contralateral to the recent one, resulting in motor deficits contralateral to the earlier lesions. Moreover, functional neuroimaging findings indicated an active crossed corticospinal tract in all of the examined patients. Both findings suggest the contribution of the uncrossed corticospinal tract contralateral to stroke lesions as a post-stroke compensatory motor system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
(62 reference statements)
2
19
0
Order By: Relevance
“…Consistent with previous studies [5, 11], most patients in our study (72.7%, N = 16) showed history of stroke and it caused limb paralysis contralateral to responsible lesions. Besides that, previous strokes were contralateral to the side of the recent stroke in 14 out of 16 patients (87.5%), suggesting that recurrent deficit occurring in the same limb from previous stroke in those cases, and past strokes or brain injury contralateral to recent strokes might be associated with the pathogenesis of motor deficits ipsilateral to recent lesions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous studies [5, 11], most patients in our study (72.7%, N = 16) showed history of stroke and it caused limb paralysis contralateral to responsible lesions. Besides that, previous strokes were contralateral to the side of the recent stroke in 14 out of 16 patients (87.5%), suggesting that recurrent deficit occurring in the same limb from previous stroke in those cases, and past strokes or brain injury contralateral to recent strokes might be associated with the pathogenesis of motor deficits ipsilateral to recent lesions.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, most cases demonstrated small patchy lesions (Fig. 1), and the recent responsible lesions located along pyramidal tract, which is consistent with findings of previous studies [5]. However, only patient 3 shows bilateral hemiparesis due to unilateral stroke, no obvious motor deficits contralateral to infarct were observed in the other 21 cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ipsilateral hemiparesis is also reported with previous contralateral infarcts possibly from disruption of compensating normal uncrossed corticospinal fibres. 2 This patient has no baseline impairment and demonstrates nondecussating tracts as an anatomical variant.…”
mentioning
confidence: 85%
“…Demirtastatlidede et al 2015 [46] explicated that 1-Hz rTMS in the affected contralesional hemisphere may help transform the neuroplasticity of patients with severe chronic stroke. LF-rTMS-enhanced exercise training could improve the dyspraxia of patients with severe upper limb dyspraxia after a chronic stroke [47].…”
Section: Rtms On Motor-function Recovery After Chronic Strokementioning
confidence: 99%